Pembuatan Indeks Beranotasi Film Karya Mahasiswa Jurusan Televisi dan Film di Institut Seni Indonesia (ISI) Padang Panjang - Fauziyah, Fauziyah; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This papers discusses about the making of annotation the work of students from the Department of Television and Film, Indonesian Institue of the Arts, Padangpanjang. This paper aims to describe the manufacture ofannotation the work of students from the Department of Television and Film, Indonesian Institue of the Arts, Padangpanjang, in order to make it easier to find information needed at any time.Data collected through observasion or research directly and documentation in the reading room of Departmen of Television and Film, Indonesia Institute of the Arts, Padangpanjang. Analysis data used the descriptive method. From the analysis of data through observasion and documentation, collected as many as 66 a collection of a movie with the subject of action, documentary, drama, horror, and thriller. Based on data analysis, can be concluded that measures in the manufacture of the annotated the movie as follows : (a) the observations of the beginning of a collection of film collection; (b) selection of the movie will be indexed; (c)recording the description of the collection ofÂ  film; (d) the making annotations film; (e) determine the keywords ; (f) creation index of film; (g) compile the index of film; (h) typing of the index.Â Keyword: Index, film, movie, annotation